SNX17 produces anti-arrhythmic effects by preserving functional SERCA2a protein in myocardial infarction. (1st December 2018) - Zhao, Dandan; Li, Xuelian; Liang, Haihai; Zheng, Nan; Pan, Zhenwei; Zhou, Yuhong; Liu, Xiao; Qian, Ming; Xu, Bozhi; Zhang, Ying; Feng, Ying; Qili, Muge; et al.
Abstract: Background: Sorting nexin 17 (SNX17) is a critical cytoplasmic adaptor protein that regulates endosomal trafficking of membrane proteins to determine their recycling and/or degradation. The potential role of SNX17 in cardiovascular pathophysiology has not been reported. Methods and results: Cardiac arrhythmias were monitored using standard limb lead II electrocardiograph, and cardiac performances were determined by echocardiography in a rat model of myocardial infarction (MI) created by left anterior descending coronary artery ligation. We found that SNX17 was substantially downregulated in ischemic myocardium. The downregulation contributed to the cardiac electrical disturbances and contractile dysfunction as SNX17 replacement mitigated the detrimental alterations of MI hearts. Specifically, silence of SNX17 expression using RNA interference caused intracellular Ca 2+ overload as revealed by the abnormal rise of resting [Ca 2+ ]i and deceleration of Ca 2+ decay, whereas SNX17 overexpression using vectors elicited the opposite effects. Moreover, the protein level of SERCA2a was significantly decreased by silencing SNX17. Immunohistochemistry indicated that SNX17 and SERCA2a were co-localized, and co-immunoprecipitation revealed the binding between the phox-homology domain of SNX17 and SERCA2a protein. Furthermore, lysosome inhibitor chloroquine prevented SNX17 silencing-induced reduction of SERCA2a protein level. Conclusion: Abnormal downregulation of SNX17 contributes to ischemic damages of cardiac electrophysiology and contractile function. SNX17 is an endogenous anti-arrhythmic factor acting by preserving functional SERCA2a protein in MI thereby offering a new strategy for the management of MI to alleviate ischemic myocardial injuries. Highlights: SNX17, a member of SNXs family, has been established playing a fundamental role in endosomes recycling and lysosomal degradation relevance to diversity of human diseases. Our findings unexpectedly reveal that a unique aspect of the SNX17-dependent management is the judgement of cardiomyocyte fate. The deficiency of SNX17 initiates SERCR2a protein downregulation by disturbing intracellular proper transport of SERCA2a. A plausible underlying mechanism arouse in this study is supplement of SNX17 stabilize the intracellular calcium disorders by recovering the SERCA2a protein level in setting of myocardial infarction. Considering that SNX17 is the guarantee of SERCA2a performance, aiming directly at SNX17 might offer a safe and efficient intervention and therapeutic strategy for SERCA2a-associated cardiovascular diseases.